Adaptable Fast Relaxing Boronate‐Based Hydrogels for Probing Cell–Matrix Interactions. Issue 9 (26th July 2018) - Tang, Shengchang; Ma, Hao; Tu, Hsiu‐Chung; Wang, Huei‐Ren; Lin, Po‐Chiao; Anseth, Kristi S.
Abstract: Hydrogels with tunable viscoelasticity hold promise as materials that can recapitulate many dynamic mechanical properties found in native tissues. Here, covalent adaptable boronate bonds are exploited to prepare hydrogels that exhibit fast relaxation, with relaxation time constants on the order of seconds or less, but are stable for long‐term cell culture and are cytocompatible for 3D cell encapsulation. Using human mesenchymal stem cells (hMSC) as a model, the fast relaxation matrix mechanics are found to promote cell–matrix interactions, leading to spreading and an increase in nuclear volume, and induce yes‐associated protein/PDZ binding domain nuclear localization at longer times. All of these effects are exclusively based on the hMSCs' ability to physically remodel their surrounding microenvironment. Given the increasingly recognized importance of viscoelasticity in controlling cell function and fate, it is expected that the synthetic strategies and material platform presented should provide a useful system to study mechanotransduction on and within viscoelastic environments and explore many questions related to matrix biology. Abstract : Adaptable, fast relaxing hydrogels are prepared from reversible boronate bonds to mimic the dynamic mechanical properties of native tissues. Control over the network viscoelasticity is realized by exploring the fundamental structure–property relationship. The fast gel relaxation maintains high viability of encapsulated mesenchymal stem cells and promotes cell–matrix mechanical signaling through physically remodeling the microenvironment across multiple time scales.